2008
DOI: 10.1042/bj20080630
|View full text |Cite
|
Sign up to set email alerts
|

Ins(1,4,5)P3 3-kinase-A overexpression induces cytoskeletal reorganization via a kinase-independent mechanism

Abstract: In the present study, effects of increased IP3K-A [Ins(1,4,5)P(3) 3-kinase-A] expression were analysed. H1299 cells overexpressing IP3K-A formed branching protrusions, and under three-dimensional culture conditions, they exhibited a motile fibroblast-like morphology. They lost the ability to form actin stress fibres and showed increased invasive migration in vitro. Furthermore, expression levels of the mesenchymal marker proteins vimentin and N-cadherin were increased. The enzymatic function of IP3K-A is to ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 33 publications
2
40
0
Order By: Relevance
“…Immunoprecipitations were essentially performed as described, 5 but to avoid degradation of EGFP-ITPKA, 2 mM EGTA was added to the lysis buffer. For immunoprecipitation of filamin C the anti-filamin C antibody from goat (Sc-48496, Lot#C0909, Santa Cruz, SC) was used.…”
Section: Immunoprecipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoprecipitations were essentially performed as described, 5 but to avoid degradation of EGFP-ITPKA, 2 mM EGTA was added to the lysis buffer. For immunoprecipitation of filamin C the anti-filamin C antibody from goat (Sc-48496, Lot#C0909, Santa Cruz, SC) was used.…”
Section: Immunoprecipitationmentioning
confidence: 99%
“…We revealed that particular tumor cell lines express ITPKA and demonstrated that this ectopic expression of ITPKA increased the metastatic potential of tumor cells. Because of its F-actin bundling activity, ITPKA induces the formation of filopodia-and lamellipodia-like protrusions, 5,6 which are critical for cells to migrate. 7 This nonenzymatic migration-promoting effect of ITPKA is stimulated by its enzyme activity in response to stimulation with growth factors.…”
mentioning
confidence: 99%
“…Therefore, spermatozoa ability to fertilize is tightly associated to a remodeling in cytoskeletal compounds. It is well-known that inositols are involved in cytoskeletal reorganization and in cellular migration (Le Clainche & Carlier, 2008;Windhorst et al, 2008;Johnson & Schell, 2009), and it is likely that MI could ameliorate the fertility rate of the patients with idiopathic infertility acting both on spermatozoa cytoskeleton rearrangements and on their migratory ability.…”
Section: Discussionmentioning
confidence: 99%
“…We found ectopic expression of the neuron-specific isoform A of ITPK in particular tumor cell lines and revealed that this upregulated expression increased their metastatic potential (6)(7)(8). Therefore, we examined the mechanism underlying regulation of the ITPKA level.…”
Section: Half-life Of Itpka Protein and Mrnamentioning
confidence: 99%
“…Because of this association and its characteristic to form homodimmers, ITPKA bundles actin filaments, resulting in increased size and/or number of dendritic spines (4,5). In tumor cells that have gained the ability to express ITPKA, the F-actin bundling activity of ITPKA, and its interaction with the Factin cross-linking protein filamin C, induces the formation of new filopodia and lamellipodia (6)(7)(8). As formation of these cellular protrusions is a prerequisite for cells to migrate, the actin-modulating activity of ITPKA increases the migratory and the metastatic potential of tumor cells (6).…”
Section: Introductionmentioning
confidence: 99%